2019
DOI: 10.1111/hel.12631
|View full text |Cite
|
Sign up to set email alerts
|

A lucid review of Helicobacter pylori‐induced DNA damage in gastric cancer

Abstract: Helicobacter pylori (H pylori) is the main risk factor for gastric cancer (GC). In recent years, many studies have addressed the effects of H pylori itself and of H pylori-induced chronic inflammation on DNA damage. Unrepaired or inappropriately repaired DNA damage is one possible carcinogenic mechanism. We may conclude that H pylori-induced DNA damage is one of the carcinogenic mechanisms of GC. In this review, we summarize the interactions between H pylori and DNA damage and the effects of H pylori-induced D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…29,30 A constitutive level of endogenous DNA damage, in part, contributes to genomic instability, and is thus involved in tumorigenesis. 31 Multiple evidences have suggested that cellular DNA damage is associated with cell apoptosis. 32,33 A previous study reported that anthracyclines exert anti-cancer activity via inducing DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 A constitutive level of endogenous DNA damage, in part, contributes to genomic instability, and is thus involved in tumorigenesis. 31 Multiple evidences have suggested that cellular DNA damage is associated with cell apoptosis. 32,33 A previous study reported that anthracyclines exert anti-cancer activity via inducing DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress relevant to pathogenesis of H. pylori infection and associated gastric carcinogenesis, for instance, H. pyloriinduced DNA damages, oncogenic activation via oxidative stress, mitochondrial damages, Nrf2-mediated autophagy, and inflammasome activation, had been proved in many publications, by which antioxidants like vitamin C, vitamin E, and rebamipide had been tried for either enhancing eradication rate or relieving gastric inflammation in animals and human trial. (30)(31)(32)(33)(34)(35)(36)(37) The fact that reactive oxygen species and reactive nitrogen species produced by H. pylori damage the host cells and can result in DNA damage, while H pylori has wisely evolved to keep damaging response, while blunting the host's efforts to kill the bacteria led to the host response that dietary intake of kimchi can serve host to prevent gastric cancer. Conclusively, since oxidative stress in H. pylori infection is defined as an imbalance between excessive production of reactive oxygen and nitrogen species and depletion of antioxidative system to eliminate the reactive intermediates, kimchi significantly enriched antioxidative defense system against chronic H. pylori infection, imposing the importance of adaptive cellular mechanisms involved in disease blocking of H. pylori-associated gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ROS induce oxidative stress, which turns out to cause damages to macromolecules such as DNA, proteins and lipids [25]. Multiple studies have suggested pathogeninduced ROS role in host-cell DNA damage [26][27][28][29][30]. Elevated ROS levels have been reported in T. gondiiinfected host cells [12,31].…”
Section: Ros Contributed To Host Dna Damagementioning
confidence: 99%